Atlas obscura : Wild life : an explorer's guide to the world's living wonders - Giaimo, Cara; Foer, Joshua (Workman Publishing, 2024)
"From the bestselling authors of Atlas Obscura and Gastro Obscura, comes Wild Life, an over-the-top, dazzling collection of the world's most fascinating, most unusual, and least-understood natural wonders. It's more than a field guide--it's an adventure. From the curious minds of Atlas Obscura, authors of #1 New York Times bestselling Atlas Obscura and Gastro Obscura, comes an unputdownable tour through the world's most extraordinary natural wonders and curiosities. Learn how dung beetles navigate by the stars and trees communicate through their roots. Meet one of the strongest animals in the world: the puny peacock mantis shrimp. Visit a 44,000 year old shrub, float along flying rivers, and explore a garbage dump teeming with endangered storks. There are first-person interviews: hear from a honey hunter and his avian partners, a scientist working to understand the hidden language of prairie dogs, an offshore radio DJ who is at the heart of the local fishing community. Examine old examples of bird song notation written on sheet music. Featuring over 500 extraordinary plants, animals, and natural phenomena with illustrations and photos on every page, first-person interviews, and engaging infographics, the book takes readers around the globe, with stops in every continent--from Arctic deserts to lush jungles, to the deepest fathoms of the ocean, and into the heart of our densest cities. In a time where the world that feels more knowable than ever, where can access anything with the click of a mouse or a swipe of a finger, and where nature documentaries are a dime a dozen, Wild Life finds a way to reinvigorate our send of wonder about the natural world"--